2007
DOI: 10.1096/fj.07-9209com
|View full text |Cite
|
Sign up to set email alerts
|

The serotonin 5‐HT2Breceptor controls bone massviaosteoblast recruitment and proliferation

Abstract: The monoamine serotonin (5-HT), a well-known neurotransmitter, is also important in peripheral tissues. Several studies have suggested that 5-HT is involved in bone metabolism. Starting from our original observation of increased 5-HT(2B) receptor (5-HT(2B)R) expression during in vitro osteoblast differentiation, we investigated a putative bone phenotype in vivo in 5-HT(2B)R knockout mice. Of interest, 5-HT(2B)R mutant female mice displayed reduced bone density that was significant from age 4 months and had int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
102
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(110 citation statements)
references
References 44 publications
5
102
0
3
Order By: Relevance
“…Indeed, pioneer work by Jean Lauder and coworkers (42,43) revealed that 5-HT regulates basic developmental processes, including cell proliferation, in mammalian and nonmammalian species. Also, identification and characterization of a 5-HT 2A signaling pathway by Sonier et al (9) demonstrated that 5-HT regulates proliferation of a human breast cancer cell line, and Collet et al (10) showed that decreased bone formation in aging female 5-HT 2B knockout mice was associated with reduced osteoblast proliferation.…”
Section: -Ht or A 5-ht 2 Agonist Increases The Proliferative Capacitmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, pioneer work by Jean Lauder and coworkers (42,43) revealed that 5-HT regulates basic developmental processes, including cell proliferation, in mammalian and nonmammalian species. Also, identification and characterization of a 5-HT 2A signaling pathway by Sonier et al (9) demonstrated that 5-HT regulates proliferation of a human breast cancer cell line, and Collet et al (10) showed that decreased bone formation in aging female 5-HT 2B knockout mice was associated with reduced osteoblast proliferation.…”
Section: -Ht or A 5-ht 2 Agonist Increases The Proliferative Capacitmentioning
confidence: 99%
“…Accordingly, and depending on its location, 5-HT may act as a neurotransmitter, a hormone, or a growth factor to regulate a wide range of cellular processes. Through activation of receptors of the 5-HT 2 subtype, 5-HT is known to have a mitogenic effect on a number of cell types, including vascular smooth muscle cells, trophoblast cells, osteoblasts, and cardiomyocytes (8)(9)(10)(11). Availability of 5-HT depends on the expression of the enzyme tryptophan hydroxylase (TPH), which catalyses the first and rate-limiting step in the biosynthesis of 5-HT (12).…”
mentioning
confidence: 99%
“…5-Hydroxytryptamine (5-HT, 2 serotonin) is well established as a neurotransmitter and a paracrine factor with over 90% of 5-HT produced by the gastrointestinal tract (1,2). There is now substantial evidence that, together with these established functions, 5-HT is involved in the control of cell proliferation through various 5-HT receptors, in particular the 5-hydroxytryptamine receptor 2B (5-HT 2B (3)(4)(5)(6)(7)(8)(9)). The 5-HT 2B receptor is G q/11 protein-coupled.…”
mentioning
confidence: 99%
“…Activation of the 5-HT 2B receptor regulates cardiac function, smooth muscle contractility, vascular physiology, and mood control. Recently it was demonstrated that activation of the 5-HT 2B receptor also induces proliferation of neurons, retinal cells (3,4), hepatocytes (5), osteoblasts (8), and interstitial cells of Cajal (ICC) (9). ICC express the 5-HT 2B receptor, and activation by 5-HT induces proliferation of ICC (9).…”
mentioning
confidence: 99%
“…Elevated levels of AOPPs are detected in many types of diseases, including osteoporosis (9)(10)(11)(12)(13)(14). Certain studies have demonstrated that oxidative stress leads to increased levels of AOPPs in osteoblastic MC3T3-E1 cells (15,16); AOPPs have been shown to inhibit the proliferation and differentiation of rat osteoblastic cells through NF-κB (17); these data suggest that AOPPs are associated with the progression of osteoporosis.…”
Section: Introductionmentioning
confidence: 99%